The interplay between digitalization, education, and financial development: A European case study - Alexandra Horobet; Irina Mnohoghitnei; Emanuela Marinela Luminita Zlatea; Lucian Belascu (Journal of Risk and Financial Management, 2022)
The paper explores the relationship between education, digitalization, and financial development between 1996 and 2019 with the aim of showcasing the differences between developed and emerging economies in Europe. We use a Bayesian VAR framework that includes variables related to education, digitalization, and financial development, as well as several endogenous variables to control for differences between countries in terms of nominal GDP growth, unemployment rate, and trade openness. Our findings clearly demonstrate the dynamic interdependence between financial development-including its two main components, financial institutions, and financial markets, digitalization, and education. Furthermore, we find that education is a leading variable in the financial development-education-digitalization nexus, whereas financial development and digitalization are laggard variables. These findings open possibilities for influencing joint policies on digitalization, education, and financial development, particularly in emerging European countries.
Keywords: 330; financial development; financial institutions; financial markets; education; digitalization; dynamic interdependence; Bayesian VAR; impulse response